The Effect of Game Based Learning Model Assisted by Blooket Media on English Vocabulary Mastery of Elementary School Students - Dellisa Ahyani; Nadia Tiara Antik Sari; Alfiana Nurussama (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the effect of the Game Based Learning model assisted by Blooket media on the mastery of English vocabulary among fifth-grade students of SDN 2 Sindangkasih, Purwakarta Regency. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 54 students: class VA (27 students) as the experimental group and class VB (27 students) as the control group. Data were collected through pretest and posttest, analyzed using Shapiro-Wilk normality test, homogeneity test, independent sample t-test, N-Gain test, and simple linear regression with SPSS version 29. The results showed: (1) there is a significant effect of the Game Based Learning model assisted by Blooket media on students’ English vocabulary mastery with a coefficient of determination of 56.3%; (2) the improvement in vocabulary mastery in the experimental group (N-Gain 61.70%, medium category) was higher and significant compared to the control group (N-Gain 18.68%, low category) with sig. value 0.001 < 0.05. It is concluded that the Game Based Learning model assisted by Blooket media is effective in improving English vocabulary mastery among elementary school students.